El conflicto entre los derechos otorgados al titular de una obtención vegetal y las limitaciones dispuestas en el artículo 491 del Código Orgánico de la Economía Social de los Conocimientos - Pérez Zárate, María Camila (2020)
The Constitution of the Republic of Ecuador, in the second section, establishes the types of property, and provides in article 322 that intellectual property is recognized in accordance with the conditions set out by law. Intellectual property rights have been developed since the Intellectual Property Law, in force from 1998 to 2016…